Radiological Characteristics And Cognitive Disorders Of Dementia Patients At Prof. Dr. Hospital I.G.N.G Ngoerah Period September 2023 - September 2024 - Fidelya Christy Rajagukguk; Kiky Monica Soesanto; Putri Laksmidewi; Ketut Widyastuti (Green Publisher Indonesia, 2025)
Dementia is a progressive neurodegenerative disorder characterized by a decline in cognitive function. Identifying the relationship between radiological characteristics and the level of cognitive impairment can help early detection and intervention planning. This study aims to describe the radiological characteristics and level of cognitive impairment in dementia patients at Prof. Dr. I.G.N.G Ngoerah Hospital during the period September 2023-September 2024. The method used was a retrospective descriptive study of 31 patients who had been diagnosed with dementia at the Neurobehaviour polyclinic. The level of cognitive impairment was categorized into mild, moderate, and severe based on the MoCA-Ina score. Radiological characteristics were assessed through Global Cortical Atrophy (GCA), Medial Temporal Atrophy (MTA), Fazekas, and Koedam scores. Results showed that MTA scores tended to increase with the severity of cognitive impairment, with the severe dementia group having an MTA score of 4 at 100%. This finding indicates that a high MTA score is associated with a more severe decline in cognitive function. The implication of this study is the importance of brain radiology examination in predicting the progression of dementia, so that early interventions can be made to slow cognitive decline.